The historic repair and reuse of Byzantine wooden bookboards in the manuscript collection of the monastery of St Catherine, Sinai - Honey, A; Velios, A (Archetype Publications, 2009)
This paper discusses the historic repair and reuse of wooden bookboards on Byzantine Greek-style bookbindings in the library of the monastery of St Catherine, Sinai. It is based on a detailed condition survey of the monastery’s manuscripts that also provided a comprehensive description of the materials and structures of these manuscripts. A total of 124 wooden boards with repairs to major splits was found on 101 manuscripts. These repaired boards have been categorised by damage to the boards, information about their repair techniques and materials and the time of repair. Finally it has been possible to compare those manuscripts with repaired boards to the rest of the collection and place the repairs into a wider context of eastern Mediterranean manuscript repair and rebinding. The study of early board repairs offers new approaches to the repair of split wooden bookboards by book conservators.